Current Status of Knowledge, Skill, and Attitude of Recent Medical Graduates Regarding Medicolegal Work in Lahore City: Medicolegal Competence of Recent Medical Graduates in Lahore - Iqbal, Zubia; Zain, Aimen; Mustafa, Tayyaba Amjad; Fazal, Asiya; Hassan, Muhammad; Asif, Muhammad (Pakistan Journal of Health Sciences, 2025)
Medicolegal responsibilities, including autopsy performance, injury documentation, and courtroom testimony, are essential components of clinical practice. In Pakistan, recent medical graduates often lack adequate preparation in these areas, raising concerns about their readiness for legal and ethical duties. Objectives: To assess the knowledge, skills, and attitudes of recent medical graduates in Lahore regarding medicolegal responsibilities, and to identify gaps to inform curriculum reform. Methods: This cross-sectional descriptive study was conducted from 1 January to 31 March 2025 in Lahore General Hospital, Lahore. A total of 394 medical graduates (within two years of graduation and having completed house jobs) were selected through stratified random sampling. A validated, self-administered questionnaire assessed knowledge, skills (self-reported), and attitudes (Likert-scale items). Data were analyzed using SPSS version 26.0 at a 95% confidence level. Results: Only 28% of participants demonstrated adequate knowledge (≥70% score), with better performance in informed consent (71.1%) and death certification (62.9%), and poor understanding of sexual-assault protocols (20.6%) and injury documentation (17.5%). Just 15.2% felt confident performing medicolegal tasks, and only 12.2% had observed an autopsy. While 78% agreed that medicolegal competence is essential, only 26% felt adequately trained during medical school. Notably, 71% expressed interest in further training. Graduates from public institutions had slightly better knowledge and exposure. Conclusions: Recent medical graduates in Lahore exhibit significant gaps in medicolegal knowledge and practical readiness. Structured medicolegal education and practical exposure must be integrated into undergraduate curricula to ensure competent and legally accountable practice.